Effect of vitamin D3 supplementation on vascular and metabolic health of vitamin D–deficient overweight and obese children: a randomized clinical trial. Issue 4 (17th January 2020) - Rajakumar, Kumaravel; Moore, Charity G; Khalid, Arshad T; Vallejo, Abbe N; Virji, Mohamed A; Holick, Michael F; Greenspan, Susan L; Arslanian, Silva; Reis, Steven E
ABSTRACT: Background: Obese children are vulnerable to vitamin D deficiency and impaired cardiovascular health; vitamin D replenishment might improve their cardiovascular health. Objectives: The aims were to determine, in vitamin D–deficient overweight and obese children, whether supplementation with vitamin D3 1000 or 2000 IU/d is more effective than 600 IU/d in improving arterial endothelial function, arterial stiffness, central and systemic blood pressure (BP), insulin sensitivity (1/fasting insulin concentration), fasting glucose concentration, and lipid profile and to explore whether downregulation of adipocytokines and markers of systemic inflammation underlies vitamin D effects. Methods: We conducted a randomized, double-masked, controlled clinical trial in 225 10- to 18-y-old eligible children. Change in endothelial function at 6 mo was the primary outcome. Results: Dose–response increases in serum 25-hydroxyvitamin D concentrations were significant and tolerated without developing hypercalcemia. Changes at 3 and 6 mo in endothelial function, arterial stiffness, systemic-systolic BP, lipids, and inflammatory markers did not differ between children receiving 1000 or 2000 IU vitamin D and children receiving 600 IU. Some secondary outcomes differed between groups. Compared with the 600-IU group, central-systolic, central-diastolic, and systemic-diastolic BP was lower at 6 mo in the 1000-IU group [−2.66 (95% CI: −5.27, −0.046), −3.57 (−5.97, −1.17), and −3.28 (−5.55, −1.00) mm Hg, respectively]; insulin sensitivity increased at 3 and 6 mo and fasting glucose concentration declined at 6 mo (−2.67; 95% CI: −4.88, −0.46 mg/dL) in the 2000-IU group. Conclusions: Correction of vitamin D deficiency in overweight and obese children by vitamin D3 supplementation with 1000 or 2000 IU/d versus 600 IU/d did not affect measures of arterial endothelial function or stiffness, systemic inflammation, or lipid profile, but resulted in reductions in BP and fasting glucose concentration and in improvements in insulin sensitivity. Optimization of children's vitamin D status may improve their cardiovascular health. This trial was registered at clinicaltrials.gov as NCT01797302.